Electrode binder, electrode mixture, electrode, and battery
Patent Information
- Application Number
- CN202580024218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-26
- Publication Date
- 2026-10-30
AI Technical Summary
[0030]根据本发明,提供一种电极用粘合剂,该电极用粘合剂包含偏氟乙烯共聚物,该偏氟乙烯共聚物与集电体的粘接性优异,即使在使用表面官能团多的电极活性物质的情况下,也不易使电极合剂增稠。而且,还提供包含该电极用粘合剂的电极合剂、电极以及电池。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to adhesives for electrodes, electrode mixtures, electrodes, and batteries. Background Technology
[0002] In the electrodes of non-aqueous electrolyte secondary batteries, vinylidene fluoride polymers are mainly used as adhesives. Considering the function of bonding the active material to the current collector, the adhesive requires high adhesion. For example, Patent Document 1 describes the introduction of functional groups such as carboxyl groups into a fluorinated resin to improve adhesion to current collectors and improve solubility in solvents. Patent Document 2 describes an adhesive composition comprising a copolymer of vinylidene fluoride and a compound with a specific structure (vinylidene fluoride copolymer), and describes that this vinylidene fluoride copolymer exhibits high adhesion to the current collector.
[0003] On the other hand, with the aim of improving battery characteristics such as increasing rate capability and reducing internal resistance, an electrode using carbon-coated and miniaturized active materials was studied.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 6-172452
[0007] Patent Document 2: Japanese Patent No. 5797206 Summary of the Invention
[0008] The problem that the invention aims to solve
[0009] To improve adhesion to current collectors, etc., the vinylidene fluoride copolymer described in Patent Documents 1 and 2 was considered as an electrode binder for active materials that have undergone carbon coating treatment and particle size reduction as described above. However, the inventors conducted in-depth research and found that when an active material with many surface functional groups is mixed with a vinylidene fluoride copolymer having carboxyl groups through carbon coating treatment, the carboxyl groups of the vinylidene fluoride copolymer interact with the functional groups on the surface of the active material to form a strong network. Furthermore, when using active materials with small particle sizes, the viscosity of the slurry tends to increase. That is, by stacking them, there is a technical problem that the viscosity of the slurry tends to become very high, resulting in low operability.
[0010] The present invention was made in view of the above-mentioned technical problems. The object of the present invention is to provide an electrode adhesive comprising a vinylidene fluoride copolymer, which exhibits excellent adhesion to current collectors and does not easily thicken the electrode adhesive even when using electrode active materials with numerous surface functional groups. Furthermore, the object of the present invention is to provide an electrode mixture, an electrode, and a battery comprising the electrode adhesive.
[0011] Solution for solving the problem
[0012] [1] An electrode adhesive comprising a vinylidene fluoride copolymer having structural units derived from vinylidene fluoride and structural units derived from a vinyl compound having a carboxyl group, the vinylidene fluoride copolymer having a weight-average molecular weight Mwa of 50,000 or more, and when the vinylidene fluoride copolymer is modified with a labeling substance formed from 1-bromomethylpyrene, and the weight-average molecular weight Mwc of the carboxyl-containing vinylidene fluoride copolymer absorbing light at a wavelength of 345 nm is determined, the Mwc is less than 0.90 relative to the Mwa.
[0013] [2] The present invention provides an adhesive for electrodes according to [1], wherein Mwc is 0.25 or more relative to Mwa.
[0014] [3] The present invention provides an electrode adhesive according to any one of [1] or [2], wherein, relative to all 100.0 mol% of the total structural units of the vinylidene fluoride copolymer, the amount of the structural units derived from vinylidene fluoride is 90.0 mol% or more, and the amount of the structural units derived from the vinyl compound is 0.01 mol% or more and 0.80 mol% or less.
[0015] [4] The present invention provides an electrode adhesive according to any one of [1] to [3], wherein the vinyl compound is a compound represented by the following general formula (1).
[0016] [Chemical Formula 1]
[0017]
[0018] (in general formula (1),
[0019] R 1 R 2 R 3 Each can be independently represented by a hydrogen atom, a halogen atom, or an alkyl group having 1 or more but less than 5 carbon atoms.
[0020] X represents a hydroxyl group or -Y-COOH (where Y represents a radical).
[0021] [5] The present invention provides an electrode adhesive according to any one of [1] to [3], wherein the vinyl compound is a compound represented by the following general formula (1).
[0022] [Chemical Formula 2]
[0023]
[0024] (in general formula (1),
[0025] R 1 R 2 R 3 Each of the following can be independently represented as a hydrogen atom, a halogen atom, or an alkyl group having 1 or more but less than 5 carbon atoms. X represents a hydroxyl group or -Y-COOH (Y represents a divalent group containing either an oxygen atom or a nitrogen atom, having 1 or more but less than 10 atoms in the main chain, and having a molecular weight of 500 or less).
[0026] [6] The present invention provides an electrode compound comprising an electrode binder and an electrode active substance according to any one of [1] to [5] above.
[0027] [7] The present invention provides an electrode comprising a solid component of an electrode adhesive according to any one of [1] to [5] above.
[0028] [8] A battery comprising the electrodes described above [7].
[0029] Invention Effects
[0030] According to the present invention, an electrode adhesive is provided, comprising a vinylidene fluoride copolymer, which exhibits excellent adhesion to current collectors and does not easily thicken the electrode adhesive even when using electrode active materials with numerous surface functional groups. Furthermore, an electrode mixture comprising the electrode adhesive, an electrode, and a battery are also provided. Detailed Implementation
[0031] 1. Adhesive for electrodes
[0032] The electrode adhesive of the present invention may contain a vinylidene fluoride copolymer, which has structural units derived from vinylidene fluoride and structural units derived from vinyl compounds having carboxyl groups. The electrode adhesive may be, for example, a solid such as a powder, or a liquid. Furthermore, the electrode adhesive may consist solely of the vinylidene fluoride copolymer, and may also contain a solvent as needed. When the electrode adhesive contains a solvent, the vinylidene fluoride copolymer may be dissolved in the solvent or dispersed in the solvent.
[0033] Conventionally, when electrode binders (slurries) are prepared by mixing carboxyl-containing vinylidene fluoride copolymers with active materials such as LFP (lithium iron phosphate) that have many functional groups on their surface and small particle size, the viscosity tends to become very high. In contrast, the electrode binder of the present invention does not tend to have excessively high viscosity even when mixed with active materials such as LFP that have multiple functional groups and small particle size. The reasons for this are as follows.
[0034] The electrode adhesive of the present invention comprises a vinylidene fluoride copolymer, which is an aggregate of many polymers formed by copolymerizing at least vinylidene fluoride with a vinyl compound having a carboxyl group. The weight-average molecular weight (Mwa) of this vinylidene fluoride copolymer is 50,000 or more. Furthermore, this vinylidene fluoride copolymer comprises: a polymer containing structural units derived from vinylidene fluoride and structural units derived from vinyl compounds (referred to in this specification as a "carboxyl-containing vinylidene fluoride copolymer" or "carboxyl-containing copolymer"); and a polymer mainly composed of structural units derived from vinylidene fluoride and not containing structural units derived from vinyl compounds having carboxyl groups. Moreover, the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer, determined by the method described later, is less than 0.90 relative to the aforementioned Mwa. That is, structural units derived from the aforementioned vinyl compounds are mainly introduced into the polymer with a relatively small molecular weight. As described above, when a general vinylidene fluoride copolymer having carboxyl groups is mixed with an active material, a strong network is formed starting from the active material. Therefore, the viscosity of the electrode adhesive (slurry) becomes very high. In contrast, in the vinylidene fluoride copolymer included in the electrode adhesive of the present invention, the average polymer molecular weight of the carboxyl-containing copolymer that interacts with the active material is relatively small. Therefore, even if the carboxyl-containing copolymer interacts with the active material, it is not easy to form a strong network, and the viscosity of the slurry is not easily increased excessively. Hereinafter, the vinylidene fluoride copolymer included in the electrode adhesive of the present invention, its physical properties, and solvents will be described in detail.
[0035] (vinylidene fluoride copolymer)
[0036] As described above, a vinylidene fluoride copolymer is a copolymer formed by copolymerizing at least vinylidene fluoride with a vinyl compound having a carboxyl group. The amount of vinylidene fluoride-derived structural units in the vinylidene fluoride copolymer is preferably 90.00 mol% or more, more preferably 95.00 mol% or more and 99.98 mol% or less, relative to 100.00 mol% of all structural units in the vinylidene fluoride copolymer. If the amount of vinylidene fluoride-derived structural units is 90.00 mol% or more, the physical properties characteristic of vinylidene fluoride are readily obtained. This value can be calculated, for example, by determining the amount of structural units in the vinylidene fluoride copolymer derived from compounds other than vinylidene fluoride.
[0037] On the other hand, the amount of structural units derived from carboxyl-containing vinyl compounds in the aforementioned vinylidene fluoride copolymer is preferably 0.01 mol% or more and 0.80 mol% or less, and more preferably 0.02 mol% or more and 0.50 mol% or less, relative to 100.0 mol% of all structural units of the vinylidene fluoride copolymer. If the amount of the aforementioned structural units derived from vinyl compounds is 0.01 mol% or more, the adhesion of the vinylidene fluoride copolymer to the current collector is easily further improved when forming the electrode using an electrode adhesive. On the other hand, if the amount of the aforementioned structural units derived from vinyl compounds is 0.80 mol% or less, the increase in slurry viscosity when mixing the electrode adhesive with the active material is easily suppressed. The amount of the aforementioned structural units derived from vinyl compounds can be determined by neutralization titration or... 1 The results can be obtained using H-NMR spectra, etc.
[0038] Here, the structure of the aforementioned vinyl compound is not particularly limited, as long as it is a compound having a vinyl group capable of polymerizing with vinylidene fluoride and having a carboxyl group. It should be noted that the vinyl compound may contain one or more carboxyl groups. It should also be noted that in this specification, an anhydride structure consisting of two carboxyl groups is also treated as a type of carboxyl group. The vinylidene fluoride copolymer may contain only one structural unit derived from the vinyl compound, or it may contain two or more. Preferred examples of vinyl compounds include compounds represented by the following general formula (1).
[0039] [Chemical Formula 3]
[0040]
[0041] In general formula (1), R 1 R 2 R 3 Each of these can be independently represented by a hydrogen atom, a halogen atom, or an alkyl group having 1 or more but less than 5 carbon atoms. Examples of alkyl groups having 1 or more but less than 5 carbon atoms include straight-chain or branched alkyl groups, and specific examples include methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentyl, etc. Among these, methyl, ethyl, or butyl are preferred from the viewpoint of ease of acquisition. Furthermore, especially from the viewpoint of minimizing steric hindrance during polymerization with vinylidene fluoride, R... 1 R 2 and R 3 Each is more preferably a hydrogen atom or a methyl group, independently.
[0042] Furthermore, in the above general formula (1), X is a hydroxyl group or a group represented by -Y-COOH. Here, Y represents a radical, Y is preferably a radical containing either an oxygen atom or a nitrogen atom, Y is more preferably a radical containing either an oxygen atom or a nitrogen atom and having a main chain with 1 or more and 10 or less atoms, and Y is even more preferably a divalent radical containing either an oxygen atom or a nitrogen atom and having a main chain with 1 or more and 10 or less atoms and a molecular weight of 500 or less.
[0043] The atomic group (Y) can be linear, branched, cyclic, or a combination thereof. From the viewpoint that it is less likely to cause steric hindrance during polymerization with vinylidene fluoride, the atomic group (Y) is preferably linear or branched.
[0044] The main chain of the atomic group (Y) has 1 or more and 10 or less atoms, preferably 2 or more and 8 or less. In this specification, the main chain of the atomic group (Y) refers to the longest chain in the chain connecting the carbonyl group of general formula (1) and the carboxyl group of -Y-COOH.
[0045] Here, the aforementioned atomic group (Y) contains either or both oxygen atoms and nitrogen atoms (hereinafter, they are also collectively referred to as "heteroatoms"). The number of heteroatoms in the atomic group (Y) is preferably 1 or more and 10 or less, more preferably 1 or more and 5 or less. When the atomic group (Y) contains two or more heteroatoms, they can be the same type of atom or different types of atom. Heteroatoms can be contained in any structure (functional group) and can exist at any position within the atomic group (Y). Examples of such structures (functional groups) containing heteroatoms include ether bonds, ester bonds, carbonyl groups, carboxyl groups, amide groups, hydroxyl groups, etc. Among these, ether bonds, ester groups, carbonyl groups, carboxyl groups, amide groups, and hydroxyl groups are preferred.
[0046] The structure of the atomic group (Y) is not particularly limited. For example, it can be a structure formed by bonding a hydrocarbon group such as alkylene or alkyl with the above-mentioned structure (functional group) containing heteroatoms. It should be noted that the molecular weight of the atomic group (Y) can be less than 500, and from the point of view of polymerization reactivity, it is preferably more than 30 and less than 200.
[0047] Specific examples of compounds represented by the above general formula (1) include: (meth)acrylic acid, (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxypropyl succinic acid, 2-carboxyethyl (meth)acrylate, 2-carboxymethyl (meth)acrylate, (meth)acryloyloxyethyl phthalic acid, N-carboxyethyl (meth)acrylamide, and other (meth)acrylamide compounds. It should be noted that in this specification, (meth)acrylic acid refers to methacrylic acid, acrylic acid, or mixtures thereof; (meth)acrylate refers to methacrylate, acrylate, or mixtures thereof; and (meth)acryloyl group refers to methacryloyl group, acryloyl group, or mixtures thereof.
[0048] From the viewpoint of ease of acquisition and reactivity with vinylidene fluoride, the compound represented by the above general formula (1) is more preferably acrylic acid, acryloyloxyethyl succinic acid, acryloyloxypropyl succinic acid, 2-carboxyethyl acrylate, or 2-carboxymethyl acrylate.
[0049] The vinyl compounds with carboxyl groups mentioned above are not limited to those shown in general formula (1). Examples of vinyl compounds other than those shown in general formula (1) include: unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; unsaturated dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride; and unsaturated dicarboxylic acid monoesters such as monomethyl fumarate, monoethyl fumarate, monomethyl maleate, monoethyl maleate, monomethyl citrate, monoethyl citrate, monomethyl phthalate, monoethyl phthalate, monomethyl itaconic acid, and monoethyl itaconic acid.
[0050] Furthermore, the vinylidene fluoride copolymer may partially comprise structural units derived from compounds other than vinylidene fluoride and the aforementioned vinyl compounds having carboxyl groups (other compounds) without impairing the purpose and effects of the present invention. The vinylidene fluoride copolymer may contain only one type of structural unit derived from other compounds, or it may contain two or more types. Specifically, relative to 100.0 mol% of all structural units of the vinylidene fluoride copolymer, the total amount of structural units derived from other compounds is preferably 10.0 mol% or less, more preferably 5.0 mol% or less. Their amounts depend on... 19 F-NMR spectrum and 1 It can be determined by H-NMR spectroscopy and other methods.
[0051] Other examples of compounds include fluorinated vinyl compounds, such as those containing vinyl and fluorine atoms or fluorinated alkyl groups in one molecule. Examples of fluorinated vinyl compounds include: fluoroethylene; trifluoroethylene; tetrafluoroethylene; trifluorochloroethylene; hexafluoropropylene; and perfluoroalkyl vinyl ethers, represented by perfluoromethyl vinyl ethers. Furthermore, other examples of compounds include those containing vinyl groups but not fluorine. Examples include unsaturated hydrocarbon compounds such as ethylene and propylene.
[0052] Here, the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is preferably 50,000 or more, more preferably 100,000 or more and 5,000,000 or less, more preferably 200,000 or more and 4,000,000 or less, and particularly preferably 250,000 or more and 3,000,000 or less. If the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is 50,000 or more, the adhesion strength between the vinylidene fluoride copolymer and active materials or current collectors is easily improved. On the other hand, if Mwa is 5,000,000 or less, the viscosity of the slurry will not be too high when preparing the electrode mixture (slurry), resulting in excellent workability. In this specification, the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is a polystyrene equivalent value determined by gel permeation chromatography (GPC). In this case, N,N-dimethylacetamide is used as the eluent, and the weight-average molecular weight is determined by a differential refractive index (RI) detector.
[0053] On the other hand, the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer in the vinylidene fluoride copolymer should be less than 0.90 relative to the weight-average molecular weight (Mwa) of the aforementioned vinylidene fluoride copolymer, i.e., Mwc / Mwa < 0.90. Preferably, Mwc / Mwa is 0.25 or more and less than 0.90, more preferably 0.25 or more and less than 0.8, and even more preferably 0.25 or more and less than 0.7. As described above, if this ratio is less than 0.90, the viscosity of the slurry is less likely to increase excessively when the vinylidene fluoride copolymer is mixed with the active material to prepare the electrode mixture (slurry).
[0054] Here, the specific weight-average molecular weight (Mwc) of the carboxyl-containing copolymer is preferably 10,000 or more, more preferably 25,000 or more and 4,700,000 or less, even more preferably 50,000 or more and 3,800,000 or less, and particularly preferably 63,000 or more and 2,800,000 or less. If the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer is within this range, the above ratio (Mwc / Mwa) is likely to fall within the desired range.
[0055] In this specification, the weight-average molecular weight (Mwc) of the aforementioned carboxyl-containing copolymers is determined as follows: A labeling agent (1-bromomethylpyrene) for labeling carboxyl groups and potassium carbonate are mixed into the vinylidene fluoride copolymer, and the carboxyl groups are esterified, thereby obtaining a pyrene-modified vinylidene fluoride copolymer. Furthermore, this value is a polystyrene conversion value when GPC is performed using N,N-dimethylacetamide as the eluent and a UV / Vis detector (detection wavelength of 345 nm). It should be noted that the pyrene structure exhibits characteristic absorption in the UV / Vis region, strongly absorbing light at a wavelength of 345 nm. That is, the carboxyl groups are esterified using 1-bromomethylpyrene, thereby determining the polymeric average molecular weight (Mwc) of the carboxyl-containing copolymer.
[0056] Here, the specific logarithmic viscosity of the aforementioned vinylidene fluoride copolymer is preferably 0.3 dL / g or more and 6.0 dL / g or less, more preferably 0.5 dL / g or more and 5.0 dL / g or less, and even more preferably 0.8 dL / g or more and 4.5 dL / g or less. If the specific logarithmic viscosity is 0.5 dL / g or more, the adhesion strength between the vinylidene fluoride copolymer and active materials or current collectors is particularly easy to improve. On the other hand, if the specific logarithmic viscosity is 6.0 dL / g or less, the slurry viscosity will not be too high when preparing the electrode mixture (slurry), resulting in excellent workability. Specific logarithmic viscosity (η) i The value () represents the logarithmic viscosity. First, 80 mg of vinylidene fluoride copolymer was dissolved in 20 ml of N,N-dimethylformamide, and the viscosity was measured using an Ubbelohde viscometer in a constant temperature bath at 30°C. Then, based on the obtained value, the viscosity was calculated using the following formula.
[0057] η i =(1 / C)・ln(η / η0)
[0058] In the above formula, η is the solution viscosity, η0 is the viscosity of N,N-dimethylformamide alone as a solvent, and C is the concentration of vinylidene fluoride copolymer in the solution, i.e., 0.4 g / dl.
[0059] Furthermore, the melting point of the vinylidene fluoride copolymer is preferably 150°C or higher and 180°C or lower, more preferably 155°C or higher and 175°C or lower, and particularly preferably 160°C or higher and 175°C or lower. If the melting point of the vinylidene fluoride copolymer is 150°C or higher, when the electrode binder (vinylidene fluoride copolymer) is used as the electrode, it is less prone to swelling due to the electrolyte, and the performance of the resulting battery tends to be better. On the other hand, if the melting point is 180°C or lower, the flexibility during electrode formation tends to be better. The melting point of the aforementioned vinylidene fluoride copolymer can be determined by heat measurement using a differential scanning calorimeter (DSC).
[0060] The aforementioned vinylidene fluoride copolymers can be prepared by copolymerizing vinylidene fluoride, the aforementioned carboxyl-containing vinyl compounds, and other compounds as needed. Examples of methods for copolymerizing these include suspension polymerization, emulsion polymerization, solution polymerization, etc., but suspension polymerization is preferred from the viewpoint of reducing impurities.
[0061] In suspension polymerization using water as the dispersion medium, suspending agents such as methylcellulose, propoxylated methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, polyvinyl alcohol, polyethylene oxide, and gelatin are added in the range of 0.005 to 1.0 parts by weight, preferably 0.01 to 0.4 parts by weight, relative to 100 parts by weight of all monomers used in the copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers).
[0062] As polymerization initiators, diisopropyl peroxide, di-n-propyl peroxide, di-n-heptafluoropropyl peroxide, isobutyryl peroxide, bis(chlorofluoroyl) peroxide, bis(perfluoroyl) peroxide, tert-butyl peroxypentanoate, etc., can be used. If all monomers used in the copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers as needed) are set at 100 parts by mass, the amount used is 0.05 to 10 parts by mass, preferably 0.15 to 5 parts by mass.
[0063] In addition, chain transfer agents such as ethyl acetate, methyl acetate, diethyl carbonate, acetone, ethanol, n-propanol, acetaldehyde, propionaldehyde, ethyl propionate, and carbon tetrachloride can be added to adjust the degree of polymerization of the obtained vinylidene fluoride copolymer. When using a chain transfer agent, if all monomers used in the copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers) are set to 100 parts by mass, the amount used is 0.01 to 5 parts by mass, preferably 0.01 to 3 parts by mass.
[0064] Furthermore, the total amount of all monomers used in the copolymerization (vinylidene fluoride, vinyl compounds with carboxyl groups, and other monomers) is typically 1:1 to 1:10, preferably 1:2 to 1:5, based on the total monomer:water mass ratio.
[0065] The polymerization temperature T is based on the 10-hour half-life temperature T of the polymerization initiator. 10 Appropriate selection, usually in T 10 -25℃≤T≤T 10 The range of +25℃ is selected. For example, the T range of tert-butyl peroxypentanoate and diisopropyl peroxydicarbonate. 10 The temperatures are 54.6℃ and 40.5℃ respectively (refer to the Nippon Oil Company product catalog). Therefore, in polymerizations using tert-butyl peroxypentanoate and diisopropyl peroxydicarbonate as polymerization initiators, the polymerization temperatures T are appropriately selected within the ranges of 29.6℃≤T≤79.6℃ and 15.5℃≤T≤65.5℃, respectively. There are no particular limitations on the polymerization time, but considering factors such as productivity, it is preferably less than 100 hours. The polymerization pressure is usually applied under pressure, preferably 2.0~10.0 MPa-G.
[0066] Here, as a method to set the weight-average molecular weight (Mwc) of the aforementioned carboxyl-containing copolymer to be less than 0.90 relative to the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer, two methods can be listed below. However, this method is not limited to any particular method. The first method involves mixing vinylidene fluoride (and other compounds) with a full amount of a carboxyl-containing vinyl compound and then initiating polymerization. The second method involves polymerizing vinylidene fluoride (and other compounds) to a certain extent, then adding the full amount of a carboxyl-containing vinyl compound to the reaction system within a short time, and further polymerizing. Examples of adding within a short time include setting the addition rate of the carboxyl-containing vinyl compound to 0.2 parts by mass per hour or more when the total monomers used for copolymerization are set to 100 parts by mass. This allows the weight-average molecular weight (Mwc) to be within a desired range. Furthermore, the weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer can be adjusted by the polymerization initiation dose, chain transfer dose, polymerization temperature, etc.
[0067] (solvent)
[0068] As mentioned above, the adhesive for the electrode may also contain a solvent. The solvent can be a non-aqueous solvent or water. Furthermore, the non-aqueous solvent can be a polar solvent. Examples of such polar solvents include: amide compounds such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; alcohol compounds such as methanol, ethanol, isopropanol, 2-ethyl-1-hexanol, 1-nonanol, lauryl alcohol, and tripropylene glycol; amine compounds such as o-toluidine, m-toluidine, and p-toluidine; imide compounds such as 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide; lactone compounds such as γ-butyrolactone and δ-butyrolactone; sulfoxide / sulfone compounds such as dimethyl sulfoxide and sulfolane; ether compounds such as tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dimethyl ether; and ketone compounds such as acetone, 2-butanone, methyl isobutyl ketone, and cyclohexanone. The adhesive for electrodes may contain only one of the above-mentioned solvents, or it may contain two or more of them.
[0069] When the electrode adhesive contains a solvent, the amount of solvent in the electrode adhesive is preferably 50 parts by mass or more and 10,000 parts by mass or less, more preferably 100 parts by mass or more and 5,000 parts by mass or less, relative to 100 parts by mass of the aforementioned vinylidene fluoride copolymer. If the amount of solvent in the electrode adhesive is within this range, the vinylidene fluoride copolymer can be uniformly dispersed or dissolved in the solvent.
[0070] (other)
[0071] The electrode adhesive may further include, without prejudice to the purpose and effect of the present invention, other resins such as acrylic resin, fillers such as inorganic fillers, dispersants, emulsifiers and various additives.
[0072] 2. Electrode mixture
[0073] The aforementioned electrode binder can be mixed with active materials (positive or negative electrode active materials) to prepare an electrode mixture (slurry) for manufacturing electrodes for non-aqueous electrolyte secondary batteries. The electrode mixture may further include conductive additives, solvents, and other additives.
[0074] The amount of solid components (excluding volatile components) derived from the electrode adhesive, active material, and conductive additives is preferably 0.2% by mass or more and 20% by mass or less, more preferably 0.2% by mass or more and 10% by mass or less, and even more preferably 0.2% by mass or more and 7% by mass or less, relative to the total amount of solid components (vinylidene fluoride copolymer) derived from the electrode adhesive.
[0075] Furthermore, the vinylidene fluoride copolymer contained in the aforementioned electrode binder is not prone to thickening or gelation of the electrode mixture even when mixed with carbon-coated active materials with surface functional groups and small particle sizes (such as LFP and LFMP (lithium iron manganese phosphate)). For example, LFP, using pure water as the dispersion medium, has an average particle size of less than 15 μm, typically between 0.1 μm and 15 μm, as determined by particle size distribution measurement based on laser backscattering / scattering. The aforementioned electrode binder is not prone to thickening of the electrode mixture even when mixed with such active materials. The average particle size of the active material is not limited to the aforementioned range.
[0076] In this invention, various active materials can be used as the electrode compound. The active material is not particularly limited and can be any known negative electrode active material or positive electrode active material.
[0077] Examples of negative electrode active materials include: carbon materials such as artificial graphite, natural graphite, difficult-to-graphitize carbon, easily-graphitize carbon, activated carbon, or substances formed by sintering and carbonizing phenolic resins and asphalt; metal / alloy materials such as Cu, Li, Mg, B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Cd, Ag, Zn, Hf, Zr, and Y; and metal oxides such as GeO, GeO2, SnO, SnO2, PbO, and PbO2. Furthermore, negative electrode active materials can also be substances coated on the surface of the aforementioned carbon materials, metal / alloy materials, and metal oxides. It should be noted that negative electrode active materials can be commercially available products.
[0078] On the other hand, examples of the positive electrode active material include lithium-based positive electrode active materials containing lithium. Examples of the lithium-based positive electrode active material include: LiCoO2, LiNi x Co y Mn 1-x-y O2 (0<x<1, 0<y<1), LiNi x Co y Al 1-x-y O2 (0<x<1, 0<y<1), LiNi x Co 1-x O2 (0<x≤1) and other composite metal chalcogenides represented by the general formula LiMY2 (M is one or more transition metals selected from Co, Ni, Fe, Mn, Cr, Ti and V, and Y is a chalcogen element such as O and S); composite metal oxides forming a spinel structure such as LiMnO2 and LiMn2O4; olivine-type lithium compounds represented by LiMaPO4 (where Ma is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr), such as LiFePO4 and LiFeMnPO4; lithium-excess solid solution positive electrodes represented by Li2MnO3-LiMbO2 (Mb=Mn, Co, Ni); lithium titanate (Li4Ti5O 12 ), titanium oxide (TiO2); Li s Ni t Co u Al v O2 (0.9<s<1.3, 0.9<t+u+v<1.1); lithium metal oxides represented by LiNi x Co y M z O2 (M represents Mn or Al, and x, y and z satisfy 0<x<1, 0<y<1, 0<z<1 and x+y+z=1) and the like. Among these, from the viewpoint of easily obtaining the effects of the present invention, LiFePO4 (LFP) and LiFeMnPO4 (LFMP), which have a small particle size and whose active material surface is covered with carbon to have a large number of surface functional groups, are particularly preferable. In addition, the positive electrode active material may also be a material obtained by coating the surface of the above-mentioned compound. Moreover, the positive electrode active material may be a commercially available product.
[0079] The amount of the active material contained in the electrode mixture is appropriately selected according to the use of the electrode mixture and the like, and is preferably 50% by mass or more and 99.9% by mass or less with respect to the total amount of the solid component derived from the above-mentioned binder for electrodes, the active material, and the conductive auxiliary agent. When the amount of the active material is within the above range, for example, a sufficient charge-discharge capacity can be obtained, and the battery performance tends to be favorable.
[0080] Furthermore, there are no particular limitations on the conductive additives included in the electrode mixture, as long as they are compounds that can further improve the conductivity between the active materials or between the active materials and the current collector. Examples of conductive additives include acetylene black, Ketjen black, carbon black, graphite powder, carbon nanofibers, carbon nanotubes, and carbon fibers.
[0081] The amount of conductive additive contained in the electrode binder is appropriately selected according to its type, etc. From the viewpoint of improving both conductivity and the dispersibility of the conductive additive, the total amount of solid components, active substances and conductive additives derived from the above-mentioned electrode binder is preferably 0.1% by mass and 15% by mass or less, more preferably 0.1% by mass or more and 7% by mass or less, and even more preferably 0.1% by mass or more and 5% by mass or less.
[0082] The electrode adhesive may contain a solvent different from the solvents that may be contained in the electrode adhesives described above. The solvent may be selected from the solvents that may be contained in the adhesives described above.
[0083] There is no particular limitation on the total amount of solvent in the electrode mixture (including the amount of solvent in the electrode adhesive), but it is generally preferred to be 10 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the active material mentioned above.
[0084] The electrode binder may also contain dispersants, adhesive aids, thickeners, etc., which can be known compounds. Examples of dispersants include: polyvinylpyrrolidone, methylcellulose, propoxylated methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, polyvinyl alcohol, polyethylene oxide, polypropylene oxide, gelatin, etc. Examples of adhesive aids include: poly(meth)acrylic acid, sodium poly(meth)acrylic acid and other poly(meth)acrylic acid metal salts, carboxymethyl cellulose, etc. These amounts are not particularly limited as long as they do not impair the purpose and effects of the present invention, and are preferably 15% by mass or less relative to the total amount of solid components and active substances derived from the electrode binder.
[0085] Furthermore, the electrode binder may further include phosphorus compounds; sulfur compounds; nitrogen compounds such as amine compounds and ammonium compounds; organic acids; organic esters; various silane-based, titanium-based, and aluminum-based coupling agents; and additives such as vinylidene fluoride polymers other than the aforementioned vinylidene fluoride copolymers, polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylonitrile (PAN) resins. These are not particularly limited as long as they do not impair the purpose and effects of the present invention, and are preferably 15% by mass or less relative to the total amount of solid components and active substances derived from the electrode binder.
[0086] The above-mentioned electrode mixture can be prepared by mixing all the components simultaneously, or by mixing a portion of the components first and then mixing the remaining components.
[0087] The viscosity of the electrode mixture is not particularly limited as long as it meets the following criteria: a viscosity sufficient to prevent liquid dripping, uneven application, and delayed drying during the formation of the mixture layer; and good workability and coatability during mixture layer preparation. This viscosity was measured using an E-type viscometer at 25°C, after a 60-second holding period at 25°C, and then measured at a shear rate of 1 second. -1 The value was measured 120 seconds after the rotor began to rotate.
[0088] 3. Electrodes
[0089] The electrode mixture described above can be used to form the electrode mixture layer of various non-aqueous electrolyte secondary batteries. The electrode of a non-aqueous electrolyte secondary battery, for example, includes a current collector and an mixture layer disposed on the current collector. The electrode mixture described above can be used in the formation of the mixture layer.
[0090] • Current collector
[0091] A current collector is a terminal used to extract electricity. There are no particular limitations on the material used for a current collector; it can be made of metal foil or mesh such as aluminum, copper, iron, stainless steel, steel, nickel, or titanium, or a material with a layer containing carbon black formed on its surface. Alternatively, it can be a material formed by forming a layer containing carbon black on the surface of other media, or a material with the aforementioned metal foil or mesh applied.
[0092] • Mixture layer
[0093] The adhesive layer is formed by applying the aforementioned electrode adhesive onto the current collector and allowing it to cure. Specifically, the adhesive layer contains at least a vinylidene fluoride compound, which serves as the solid component of the aforementioned electrode adhesive, and an active substance. The adhesive layer may be formed on only one side of the current collector or on both sides.
[0094] The adhesive layer contains at least the components of the electrode adhesive described above, namely the solid components (vinylidene fluoride copolymer) derived from the electrode adhesive and active substances, and may further contain conductive additives, dispersants, adhesive aids, thickeners, and other additives as needed. These may be the same as those described in the electrode adhesive.
[0095] The thickness of the agent layer is not particularly limited here; in one example, it is preferably 1 μm or more and 1000 μm or less. Furthermore, the weight per unit area of the agent layer formed on one surface of the current collector is not particularly limited and can be any weight per unit area; in one example, it is preferably 50 g / m². 2 Above and 1000g / m 2 The following is more preferably 100g / m 2 Above and 500g / m 2 the following.
[0096] The aforementioned mixture layer can be formed by performing a process of applying the aforementioned electrode mixture onto the current collector and then curing it.
[0097] There are no particular limitations on the coating method of the electrode mixture. It can be applied by methods such as doctor blade coating, reverse roller coating, comma bar coating, gravure printing, air knife coating, mold coating, and dip coating.
[0098] Furthermore, after coating the electrode mixture, the solvent is dried by heating at any temperature. In one example, the drying temperature is preferably 60°C or higher and 500°C or lower, more preferably 80°C or higher and 200°C or lower. Heating can be performed multiple times at different temperatures. It should be noted that the solvent in the mixture can be dried under atmospheric pressure, under pressure, or under reduced pressure, or in an environment with air, nitrogen, argon, etc. Further heat treatment can be performed after drying.
[0099] After the electrode mixture is coated and dried, it can be further pressed. Pressing increases the electrode density. In one example, the pressing pressure is preferably 1 kPa or more and 10 GPa or less.
[0100] 4. Battery
[0101] As described above, the electrode adhesives and electrode binders described above can be used for electrodes of various non-aqueous electrolyte secondary batteries, and can also be used to form other layers of non-aqueous electrolyte secondary batteries.
[0102] Example
[0103] Hereinafter, specific embodiments and comparative examples of the present invention will be described together, but the present invention is not limited thereto.
[0104] (Methods for determining and evaluating physical properties)
[0105] In the examples and comparative examples described later, the amount of carboxyl-containing vinyl compounds in the vinylidene fluoride copolymer was determined by the following method ( 1The specific concentration logarithmic viscosity of the vinylidene fluoride copolymer, the weight-average molecular weight Mwa of the vinylidene fluoride copolymer, and the weight-average molecular weight Mwc of the carboxyl-containing copolymer were determined by H-NMR determination and neutralization titration. Furthermore, the slurry viscosity and peel strength of the electrode mixture were determined by the following methods.
[0106] • Determination of the amount of vinyl compounds containing carboxyl groups introduced ( 1 (H-NMR measurement)
[0107] According to the use 1 From the ¹H-NMR spectra obtained, the integrated intensities of the peaks originating from vinylidene fluoride and the peaks originating from carboxyl-containing vinyl compounds within the structural units of the vinylidene fluoride polymer were determined. Then, based on the ratio of the integrated intensities of the peaks originating from carboxyl-containing vinyl compounds to the sum of the integrated intensities of the peaks originating from vinyl compounds and the peaks originating from vinylidene fluoride in all structural units of the vinylidene fluoride polymer, the proportion (mol%) of carboxyl-containing vinyl compounds in all structural units of the vinylidene fluoride polymer was calculated. The measuring apparatus used was a nuclear magnetic resonance spectrometer (NMR, JEOL, JNM-ECZ600R / S1, frequency 600MHz), and the solvent used was DMSO-d6.
[0108] • Determination of the amount of vinyl compounds containing carboxyl groups introduced (neutralization titration)
[0109] While stirring 100 mL of acetone, add 0.50 g of the polymer, weighed precisely. Heat and stir at 50 °C until dissolved, then slowly add 5 mL of water while heating and stirring. Next, add approximately 5 drops of phenolphthalein ethanol solution as an indicator. Using a burette, add a known concentration of 0.1 N sodium hydroxide aqueous solution while stirring the solution to be titrated, and perform titration. Perform this process three times, and calculate the mole fraction of the vinyl compound based on the average value.
[0110] • Specific viscosity logarithmic viscosity
[0111] The specific logarithmic viscosity of the vinylidene fluoride copolymer was determined as follows. First, 80 mg of the vinylidene fluoride copolymer was dissolved in 20 ml of N,N-dimethylformamide, and the viscosity was measured using an Ubbelohde viscometer in a constant temperature bath at 30°C. Then, based on the obtained value, the specific logarithmic viscosity (η) of the vinylidene fluoride copolymer was calculated using the following formula. i ).
[0112] η i =(1 / C)・ln(η / η0)
[0113] In the above formula, η is the solution viscosity, η0 is the viscosity of N,N-dimethylformamide alone as a solvent, and C is the concentration of the vinylidene fluoride polymer in the solution, i.e., 0.4 g / dl.
[0114] • Weight-average molecular weight (Mwa) of vinylidene fluoride copolymer
[0115] The weight-average molecular weight (Mwa) of the vinylidene fluoride copolymers prepared in the examples and comparative examples was determined using a differential refractometer (RI). Specifically, GPC (gel permeation chromatography) was performed under the following conditions, and Mwa was determined using a differential refractometer. This process was performed three times, and the average value was taken as Mwa.
[0116] Separation chromatographic columns: Shodex KD-807, KD-806M.
[0117] Detector: RI-4030 (differential refractive index detector) manufactured by Japan Spectrophotometer Co., Ltd.
[0118] Eluent: 10 mM LiBr-N,N-dimethylacetamide (DMAc) solution.
[0119] Flow rate of elution buffer: 0.5 mL / min.
[0120] Column temperature: 40℃.
[0121] The standard polymer used for calibration curves is TSK standard POLY (STYRENE) (manufactured by Tosoh Corporation).
[0122] • Weight-average molecular weight (Mwc) of carboxyl-containing copolymers
[0123] 10 mg of the vinylidene fluoride copolymer prepared in each example and comparative example, 2 mg of 1-bromomethylpyrene, and 2 mg of potassium carbonate were added to 10 mg of DMAc. The mixture was stirred in a constant-temperature shaking bath at 50°C for 3 hours for dissolution / reaction. The potassium carbonate was removed using a 0.45 μm filter. Thus, the carboxyl groups of the carboxyl-containing copolymers in the vinylidene fluoride copolymers were labeled with 1-bromomethylpyrene.
[0124] The weight-average molecular weight (Mwc) of the carboxyl-containing copolymer (polymer absorbing light at a wavelength of 345 nm) of the 1-bromomethylpyrene-labeled vinylidene fluoride copolymer was determined using a UV-vis detector (UV-4075, Nippon Spectrophotometer). Except for the detector, the determination was performed under the same conditions as for Mwa described above. The detection wavelength was set to 345 nm, and the weight-average molecular weight (Mwc) of the carboxyl-containing copolymer was calculated. This process was performed three times, and the average value was taken as Mwc.
[0125] • Slurry viscosity
[0126] The viscosity of the electrode mixture prepared in the examples and comparative examples was measured when the electrode mixture was freshly manufactured.
[0127] Specifically, the viscosity of the electrode mixture was measured immediately after it was prepared. The freshly prepared electrode mixture was placed into an E-type viscometer (Toki Sangyo Co., Ltd. RE-215R type viscometer, rotor 3°×R14). After being held at 25°C for 60 seconds, the viscosity was measured at a shear rate of 1 second. -1 Rotate the rotor and determine the viscosity of the slurry 120 seconds after the rotor starts rotating.
[0128] • Peel strength
[0129] The electrode mixtures prepared in the examples and comparative examples were applied to 16 μm thick aluminum foil using a rod coater and dried at 110°C for 30 minutes, thereby obtaining a weight per unit area of 160 g / cm³. 2 A single-sided coated electrode was prepared. The resulting single-sided coated electrode was cut into pieces with a length of 70 mm and a width of 20 mm, and the peel strength between the aluminum foil and the adhesive layer was evaluated. Specifically, the upper surface of the formed adhesive layer was bonded to a thick plastic sheet (acrylic resin, 5 mm thick), and a 90° peel test was performed using a tensile testing machine (Orientec STA-1150 single-column material testing machine) at a clamping speed of 10 mm / min, according to JIS K6854-1. It should be noted that the test environment was an operating temperature of 25°C and a dew point of -20°C.
[0130] (Example 1)
[0131] [Preparation of vinylidene fluoride copolymer (electrode binder)]
[0132] 1240 g of ion-exchanged water (as dispersion medium), 0.4 g of Metrolose SM-100 (Shin-Etsu Chemical Co., Ltd.) (as cellulose-based suspending agent), 2.0 g of acryloyloxypropyl succinic acid (APS), 0.6 g of a 50 wt% diisopropyl peroxide-HFE-347 pc-f solution (as polymerization initiator), 0.72 g of ethyl acetate (as chain transfer agent), and 400 g of vinylidene fluoride were added to a 2-liter autoclave. The mixture was heated to 45°C over 2 hours. While maintaining the temperature at 45°C, the reaction continued until the pressure in the system decreased to 1.5 MPaG.
[0133] After polymerization, the polymer slurry was heat-treated at 95°C for 60 minutes. Then, it was dehydrated, washed with water, and further dried at 80°C for 20 hours to obtain a powder of vinylidene fluoride copolymer (electrode binder) as a copolymer of vinylidene fluoride (VDF) and APS. The amount of carboxyl-containing vinyl compounds introduced was determined by... 1The values were calculated by ¹H-NMR determination. Table 1 shows the amount of carboxyl-containing vinyl compounds introduced into the vinylidene fluoride copolymer, its specific logarithmic viscosity, weight-average molecular weight Mwa, and the weight-average molecular weight Mwc of the carboxyl-containing copolymers contained therein. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 4% by mass and used as an adhesive solution.
[0134] [Preparation of Electrode Mixture]
[0135] LFP (carbon coating: 1.4%, average particle size D50: 4 μm) was used as the electrode active material, and carbon nanotubes (CNT: Cano LB107-44) were used as the conductive additive. NMP was used as the dispersion medium. The amount of NMP was adjusted using an E-type viscometer to achieve a slurry viscosity of 8000–30000 mPa·sec at 25°C and a shear rate of 1 / sec. The binder solution, LFP, and CNT were then mixed to prepare the electrode mixture. The mass ratio of LFP, CNT, and PVDF in the resulting electrode mixture was 100:2:2.5, and the solids concentration was 52.0% by mass. The slurry viscosity at this point is shown in Table 1.
[0136] [Electrode manufacturing]
[0137] The obtained electrode mixture was coated onto the current collector (a 16 μm thick carbon-coated aluminum foil) using a rod coater. The mixture was then dried at 110°C for 30 minutes under a nitrogen atmosphere in a constant temperature bath, yielding a dried mixture with a unit area weight of 160 g / m². 2 The electrodes.
[0138] (Example 2)
[0139] 1034 g of ion-exchanged water (as dispersion medium), 0.47 g of Metrolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.) (as cellulose-based suspending agent), 1.65 g of a 50 wt% diisopropyl peroxide-HFE-347pc-f solution (as polymerization initiator), and 470 g of vinylidene fluoride were added to a 2-liter autoclave. The temperature was raised to 26°C over 55 minutes. Maintaining the temperature at 26°C, the temperature was raised to 40°C over 63 minutes, starting from the point where the pressure decreased by 0.2 MPaG at the end of the heating process. During this process, 1.18 g of a 5 wt% APS aqueous solution (based on solute conversion) was added. The reaction was continued while maintaining the temperature at 40°C until the pressure in the system decreased to 1.58 MPaG.
[0140] The obtained polymer slurry was processed in the same way as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0141] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 4% by mass and used as an adhesive solution.
[0142] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 1 above.
[0143] (Comparative Example 1)
[0144] 1143 g of ion-exchanged water (as dispersion medium), 0.21 g of Metrolose SM-100 (Shin-Etsu Chemical Co., Ltd.) (as cellulose suspending agent), 0.13 g of APS, 2.10 g of a 50 wt% diisopropyl peroxide-HFE-347pc-f solution (as polymerization initiator), and 420 g of vinylidene fluoride were added to a 2-liter autoclave. The temperature was raised to 26°C over 55 minutes. While maintaining the temperature at 26°C, 0.92 g of a 5 wt% APS aqueous solution (calculated as solute) was added over 4.3 hours, starting 2 hours after the start of heating. From the point where the pressure decreased by 0.2 MPaG at the end of the heating process, the temperature was raised to 40°C over 120 minutes. While maintaining the temperature at 40°C, the reaction continued until the pressure in the system decreased to 1.3 MPaG.
[0145] The obtained polymer slurry was processed in the same way as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0146] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 4% by mass and used as an adhesive solution.
[0147] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 1 above. However, the slurry of the electrode mixture using this vinylidene fluoride copolymer had a high viscosity, and due to poor dispersion, it produced pitting during electrode fabrication, making it difficult to apply evenly.
[0148] (Example 3)
[0149] The amount of 50wt% diisopropyl peroxide dicarbonate-HFE-347pc-f solution as the polymerization initiator was set to 1.40g, and the amount of ethyl acetate was set to 0.80g. Otherwise, polymerization and post-polymerization treatment were carried out in the same manner as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0150] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 5% by mass and used as an adhesive solution.
[0151] Using this vinylidene fluoride copolymer, the solids concentration of the electrode mixture is 55.0% by mass. Otherwise, the electrode mixture and electrode are manufactured in the same manner as in Example 1 above.
[0152] (Comparative Example 2)
[0153] Before heating began, a 50 wt% solution of diisopropyl peroxide dicarbonate-HFE-347pc-f containing 0.07 g of APS and 3.15 g of polymerization initiator was added. Two hours after heating began, 0.77 g of a 5 wt% APS aqueous solution (calculated as solute) was added over a period of 4.3 hours. Otherwise, polymerization and post-polymerization treatment were carried out in the same manner as in Comparative Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0154] The obtained polymer slurry was processed using the same method as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0155] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 5% by mass and used as an adhesive solution.
[0156] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 3 above.
[0157] (Example 4)
[0158] The APS charge was set to 2.12 g and the ethyl acetate charge was set to 1.60 g. Otherwise, polymerization and post-polymerization treatment were carried out in the same manner as in Example 3 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0159] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 6% by mass and used as an adhesive solution.
[0160] Using this vinylidene fluoride copolymer, the solid content of the electrode mixture is 58.5% by mass. Otherwise, the electrode mixture and electrode are manufactured in the same manner as in Example 1 above.
[0161] (Comparative Example 3)
[0162] A 2-liter autoclave was loaded with 1085 g of ion-exchanged water as a dispersion medium, 0.21 g of Metrolose SM-100 (Shin-Etsu Chemical Co., Ltd.) as a cellulose-based suspending agent, 0.13 g of APS, 2.12 g of a 50 wt% diisopropyl peroxide-HFE-347pc-f solution as a polymerization initiator, 1.70 g of ethyl acetate as a chain transfer agent, and 4248 g of vinylidene fluoride. The autoclave was heated to 26°C over 55 minutes. While maintaining the temperature at 26°C, 12.12 g of a 5 wt% APS aqueous solution was added over 12 hours, starting 2 hours after the start of heating. From the point when the pressure decreased by 0.2 MPaG at the end of the heating process, the autoclave was heated to 40°C over 180 minutes. While maintaining the temperature at 40°C, the reaction was continued until the pressure in the system decreased to 1.3 MPaG.
[0163] The obtained polymer slurry was processed using the same method as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0164] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 6% by mass and used as an adhesive solution.
[0165] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 4 above. However, the slurry of the electrode mixture using this vinylidene fluoride copolymer had a high viscosity, making viscosity measurement impossible.
[0166] (Example 5)
[0167] 1024 g of ion-exchanged water (as dispersion medium), 0.6 g of Metrolose SM-100 (Shin-Etsu Chemical Co., Ltd.) (as cellulose-based suspending agent), 0.04 g of APS, 4.80 g of a 50 wt% di-n-propyl peroxide-methanol solution (as polymerization initiator), 1.96 g of ethyl acetate (as chain transfer agent), and 400 g of vinylidene fluoride were added to a 2-liter autoclave. The temperature was raised to 26°C over 55 minutes. Maintaining the temperature at 26°C, the temperature was raised to 55°C over 60 minutes, starting from the point where the pressure decreased by 0.2 MPaG at the end of the heating process. During this process, 3.96 g of a 5 wt% APS aqueous solution (based on solute conversion) was added. The reaction was continued while maintaining the temperature at 55°C until the pressure in the system decreased to 1.3 MPaG.
[0168] The obtained polymer slurry was processed using the same method as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0169] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 13% by mass and used as an adhesive solution.
[0170] Using this vinylidene fluoride copolymer, the electrode mixture has a mass ratio of LFP, CNT, and PVDF of 100:2:4 and a solid content of 59.0% by mass. Otherwise, the electrode mixture and electrode are manufactured in the same manner as in Example 1 above.
[0171] (Example 6)
[0172] 1034 g of ion-exchanged water (as dispersion medium), 0.47 g of Metrolose SM-100 (Shin-Etsu Chemical Co., Ltd.) (as cellulose-based suspending agent), 6.58 g of a 50 wt% diisopropyl peroxide-HFE-347pc-f solution (as polymerization initiator), 15.09 g of ethyl acetate (as chain transfer agent), and 470 g of vinylidene fluoride were added to a 2-liter autoclave. The mixture was heated to 26°C over 55 minutes. Maintaining the temperature at 26°C, the mixture was then heated to 45°C over 127 minutes, starting from the point where the pressure decreased by 0.2 MPaG at the end of the heating process. During this process, 2.35 g of a 5 wt% APS aqueous solution (based on solute conversion) was added. The reaction was continued while maintaining the temperature at 45°C until the pressure in the system decreased to 1.3 MPaG.
[0173] The obtained polymer slurry was processed using the same method as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0174] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 13% by mass and used as an adhesive solution.
[0175] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 5 above.
[0176] (Example 7)
[0177] Instead of APS, the amount of acrylic acid (AA) was set to 1.20 g, the concentration of the polymerization initiator (diisopropyl peroxide dicarbonate-HFE-347pc-f solution) was set to 2.48 g, and the amount of ethyl acetate as chain transfer agent was set to 2.60 g. Otherwise, polymerization and post-polymerization treatment were carried out in the same manner as in Example 4 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0178] The obtained polymer slurry was processed using the same method as in Example 1 to obtain a powder of vinylidene fluoride copolymer (electrode binder). In the evaluation of this vinylidene fluoride copolymer, the amount of vinyl compounds introduced was calculated by neutralization titration determination, otherwise performed in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP to a concentration of 13% by mass for use as a binder solution.
[0179] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 5 above.
[0180] (Comparative Example 4)
[0181] Before heating began, 0.21 g of APS, 5.09 g of a 50 wt% diisopropyl peroxide-HFE-347pc-f solution as a polymerization initiator, and 9.33 g of ethyl acetate as a chain transfer agent were added. Two hours after heating began, 4.03 g of a 5 wt% APS aqueous solution (calculated as solute) was added over 18 hours. Otherwise, polymerization and post-polymerization treatment were carried out in the same manner as in Comparative Example 3 to obtain a powder of vinylidene fluoride copolymer (electrode binder).
[0182] The evaluation of the vinylidene fluoride copolymer was carried out in the same manner as in Example 1. The vinylidene fluoride copolymer was then dissolved in NMP at a concentration of 13% by mass and used as an adhesive solution.
[0183] Using this vinylidene fluoride copolymer, the electrode mixture and electrode were manufactured in the same manner as in Example 5 above.
[0184] (result)
[0185]
[0186]
[0187] As shown in Tables 1 and 2 above, if the weight-average molecular weight Mwa of the vinylidene fluoride copolymer is above 50,000, and the weight-average molecular weight Mwc of the carboxyl-containing copolymer is less than 0.90 relative to Mwa, then compared with the comparative example under the same conditions of slurry composition and solid component concentration, the slurry viscosity is low and the peel strength is at the same level.
[0188] This application claims priority based on Japanese Patent Application No. 2024-056534, filed on March 29, 2024. All contents set forth in that application are incorporated herein by reference.
[0189] Industrial availability
[0190] According to the present invention, an electrode adhesive is provided, comprising a vinylidene fluoride copolymer, which exhibits excellent adhesion to current collectors and the like, and does not easily thicken the electrode adhesive even when lithium iron phosphate is used as the electrode active material. This electrode adhesive is highly useful in the manufacture of various batteries.
Claims
1. An electrode adhesive comprising a vinylidene fluoride copolymer having structural units derived from vinylidene fluoride and structural units derived from a vinyl compound having a carboxyl group. The weight-average molecular weight (Mwa) of the vinylidene fluoride copolymer is above 50,000. When the carboxyl-containing vinylidene fluoride copolymer was modified with a labeling substance formed from 1-bromomethylpyrene, and the weight-average molecular weight (Mwc) of the vinylidene fluoride copolymer that absorbed light at a wavelength of 345 nm was determined, The Mwc is less than 0.90 relative to the Mwa.
2. The electrode adhesive according to claim 1, wherein, The Mwc is greater than or equal to the Mwa.
3. The electrode adhesive according to claim 1, wherein, Relative to 100.0 mol% of all structural units of the vinylidene fluoride copolymer The amount of the structural units derived from vinylidene fluoride is 90.0 mol% or more. The amount of the structural unit derived from the vinyl compound is more than 0.01 mol% and less than 0.80 mol%.
4. The electrode adhesive according to claim 1, wherein, The vinyl compound is a compound represented by the following general formula (1). [Chemical Formula 1] In general formula (1), R 1 R 2 R 3 Each can be independently represented by a hydrogen atom, a halogen atom, or an alkyl group having 1 or more but less than 5 carbon atoms. X represents a hydroxyl group or -Y-COOH, where Y represents a radical group.
5. The electrode adhesive according to claim 1, wherein, The vinyl compound is a compound represented by the following general formula (1). [Chemical Formula 2] In general formula (1), R 1 R 2 R 3 Each can be independently represented by a hydrogen atom, a halogen atom, or an alkyl group having 1 or more but less than 5 carbon atoms. X represents a hydroxyl group or -Y-COOH, where Y represents a divalent group containing either an oxygen atom or a nitrogen atom, with a main chain having 1 or more atoms and a molecular weight of 500 or less.
6. An electrode binder comprising an electrode binder and an electrode active substance according to any one of claims 1 to 5.
7. An electrode comprising a solid component of an electrode binder according to any one of claims 1 to 5.
8. A battery comprising the electrode according to claim 7.
Citation Information
Patent Citations
Composite logarithmic period antenna
JP1982097206A
Vinylidene fluoride-based copolymer
JP1994172452A
High-speed scan fourier transform spectrometer and spectroscopy method
JP2024056534A
